Comprehensive board review in neurology - Borsody, Mark K. (Thieme, 2013)
This is a fantastic board review book that more than satisfactorily covers the material that is tested on the ABPN exam. Though not everyone has the same learning style or approach to board study, few will disagree that this is a well-written and memorable review book. It is thorough and concise, and the font and choice of colors is easy on the eyes.